Folk Medicinal Plants from Kinnaur Region of Himachal Pradesh, India - Bhardwaj, Meenakshi; Chauhan, N. S.; Pandey, Anjula (Indian Forester, 2014)
An ethnobotanical survey was carried out to collect information on the available genetic resource of medical plants of the Kinnaura schedule tribes of Himachal Pradesh, India. A total of 49 species belonging to 412 genera and 27 families were reported as being used locally for the treatment of human ailment. Out of these 25species belong to different threat categories and have already entered the list of red data book. Kinnaura tribes have a strong faith on these traditional phytotherapies and the loss or endangered d\status of these plants will affect the health care practices of these tribes to a great extent. Hence, there is an urgent need for sustainable harvest and conservation of these valuable resources. The conservation based on indigenous knowledge is recommended.